Potential mitigating role of ivermectin on the spread of Chlamydia trachomatis by Musca sorbens. - Richard Selby; Anita Jeyam; Andrew Tate; Fikreab Kebede; Philip Downs (Public Library of Science (PLoS), 2023)
Trachoma is the world's most frequent cause of blindness from an infectious agent. The disease caused by infection is associated with lack of access to sanitation and low hygiene standards. Trachoma is controlled through the Surgery, Antibiotics, Facial cleanliness, and Environmental improvement (SAFE) strategy, which delivers azithromycin (AZM) mass drug administration (MDA) in endemic areas. The putative vector Musca sorbens principally reproduce in human faecal matter left in the environment due to open defecation. Ivermectin (IVM) is on the WHO's essential medicines list and is administered as preventative chemotherapy against two neglected tropical diseases (NTDs)-onchocerciasis, as an annual or bi-annual treatment, and lymphatic filariasis, as an annual treatment in combination with albendazole. Ivermectin has a known inhibitive effect on insects that reproduce in dung. To assess if IVM could be a viable vector control tool against M. sorbens, this study evaluates existing data from trachoma, onchocerciasis and lymphatic filariasis mass drug administration (MDA) operations in Ethiopia. Persistent and recrudescent trachoma in evaluation units (EUs) were examined for whether AZM MDA in EUs was accompanied by IVM MDA, and whether co-administration was associated with greater likelihood of trachoma control. Results show an association suggesting that EUs that received both IVM and AZM MDA benefit from improved control of trachoma in persistent or recrudescent areas, when compared to EUs that received AZM MDA. This initial investigation supports the potential for ivermectin's use to support SAFE. Findings warrant further work to validate ivermectin's impact on M. sorbens reproduction through controlled lab and field-based studies.